(3QSGdI aj GdeRGQYIs - (3eMeO Hf HjQe GdKGfjs
(3ChdgG (B:s
(3SHMGf ef adb GdMH hHYO agPg QSGdI LGeYI dCMcGe UhQ GdeRGQYI VHWJ ajgG HeG de CSHb Edjg CbSGegG s
(3BNQgG (B:s
(3hCeG eG ajg JaUjd hGdKGefI hGdYTQhf hGdKdGKhf hGdJGSYI hGdKdGKhf hGdCQHYhf GdJi HgG GdNJGe GfJgi HMeO Gddg hMSf Yhfg hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG Edi jhe GdOjf s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3HjQhJ , ecJHI GdMHjH GddeSi (B- (3HjQhJ (B((3abg(B) s
Keywords: (3Gdabg GdESdGejs